Building mutual motivation and collaborating to overcome the water crisis - Nurjaya, Muhammad; Anwar (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
Clean water is one of Indonesia's main problems, particularly at the village level. The Pansimas program, facilitated by the central government, has become the primary plan to solve the problem. The central government targets 100% complete filled to the need for clean water throughout the territories. This article deals with the dynamic of the Pamsimas program's process to overcome such a problem from the grassroots level. This study was conducted at Borikamase Village, Maros Regency. Data were collected using in-depth interviews with twelve informants from various backgrounds (village head, government officials, partnership community, facilitators, non-governmental organization, public figure, religious leader, and targetted community). The study indicates that it is complicated to get clean water in Borikamase. The limitation of clean water in the village resulted in high community protection of their village's water source from outsiders. Therefore, water sources are locally termed bulaeng je'ne (golden water), which means that clean water is considered highly valued. However, It is challenging to overcome the crisis of clean water in the village because of the lack of mutual motivation among community members. This mutual motivation consists of mutual trust, mutual understanding, mutual recognition, and commitment. Therefore, it needs to strengthen the collaboration between the government and the community being targeted to the program to solve the need for clean water.